2015
DOI: 10.1155/2015/307594
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Ethanol Extracts of Chinese Propolis (Poplar Type) and Poplar Gums Based on the Antioxidant Activities and Molecular Mechanism

Abstract: The biological activities of propolis are varied from plant sources and the prominent antioxidant effects of Chinese propolis (poplar type) have been extensively reported. Oxidative stress is associated with inflammation and induces many diseases. In the study, to evaluate antioxidant capacities and clarify the underlying molecular mechanisms of ethanol extracts of Chinese propolis (EECP) and ethanol extracts of poplar gums (EEPG), we analyzed their compositions by HPLC, evaluating their free radical scavengin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 49 publications
3
46
0
Order By: Relevance
“…All the extracts from T. tetraptera may act as antioxidant by scavenging free radicals. This result corroborates previous studies which demonstrated that plant phenolic compounds could act as radical chelator [41]. …”
Section: Discussionsupporting
confidence: 93%
“…All the extracts from T. tetraptera may act as antioxidant by scavenging free radicals. This result corroborates previous studies which demonstrated that plant phenolic compounds could act as radical chelator [41]. …”
Section: Discussionsupporting
confidence: 93%
“…The same method for the TAC determination of methanol-water extracts from the black locust and poplar leaves was used by Tálos-Nebehaj et al (2017) as well as of water extracts from willow bark by Durak et al (2015) and Durak and Gawlik-Dziki (2014). The results of ABTS test of poplar buds and willow bark were also expressed as the IC 50 value (Zaiter et al 2016;Zhang et al 2015b). Todaro et al (2017) determined TAC in terms of radical scavenging ability using the stable DPPH.…”
Section: Total Antioxidant Capacity (Tac) Total Phenolic Content (Tpmentioning
confidence: 99%
“…TACs of willow and poplar leaves (Tálos-Nebehaj et al 2017), willow leaves, bark and catkins (Enayat and Banerjee 2009;Zaiter et al 2016), as well as poplar buds and Fig. 5 The structures of lignans present in willow wood poplar-type propolis (Zhang et al 2015b) were evaluated. The wavelength at which the absorbance was measured was generally 515 or 517 nm.…”
Section: Total Antioxidant Capacity (Tac) Total Phenolic Content (Tpmentioning
confidence: 99%
See 2 more Smart Citations